ChemInform Abstract: Highly Efficient Click Reaction on Water Catalyzed by a Ruthenium Complex. Issue 24 (June 2015) - Siyang, Hai Xiao; Liu, Hui Ling; Wu, Xin Yan; Liu, Pei Nian
Abstract: Various substituted 1, 4‐disubstituted triazoles (III) are obtained by highly efficient Ru‐catalyzed click reaction between terminal alkynes and organic azides.